Corpus pragmatic studies on the history of medical discourse - Hiltunen, Turo ca. 20./21. Jh; Taavitsainen, Irma 1946- (Pragmatics & beyond new series (P&BNS), 2022)
Table of contents: Corpora, pragmatics, and historical medical discourse / Turo Hiltunen and Irma Taavitsainen -- "A geography of names" : a genre analysis of nationality-driven names for venereal disease in seventeenth-century England / Tony McEnery and Helen Baker -- Medical topics and style from 1500 to 2018 : a corpus-driven exploration / Gerold Schneider -- Medical discourse in Late Modern English : insights from a multidisciplinary corpus of scientific journal articles / Katrin Menzel -- Survival or death : Mine/my and thine/thy variation in Early Modern English medical writing / Terry Walker and Merja Kytö -- Towards a local grammar of stance expression in Late Modern English medical writing / Turo Hiltunen -- "Die Blumenzeit der Frau" : a corpus-based study of the development of medical references to menstruation in historical texts on herbology / Gohar Schnelle, Carolin Odebrecht, Anke Lüdeling, Laura Perlitz and Catharina Fisher -- Language, labour and ideology : constructing epistemologies of childbirth in the first three centuries of English-language midwifery texts (1540-1800) / Richard J. Whitt -- Unhappy patients and eminent physicians : the representation of patients and practitioners in Late Modern English medical writing / Anu Lehto -- The discursive dynamics of personal experience narratives and medical advice in 18th-century British consultation letters : the case of Dr. William Cullen / Anna Franca Plastina -- Communicating authority : self-mentions in early modern English medical narratives (1500-1700) / Karoliina Ollikainen -- How old is old? The discourse of "good" ageing in nineteenth-century self-help medical texts / Kim Grego -- The popularization of learned medicine in late seventeenth-century England : accommodating translation strategies and textual aspects / Giulia Rovelli.